A Case Study of Rheumatoid Arthritis (Advancements in Homeopathic Research, 2022)
Objective: To ascertain the effectiveness of complete  repertory in case of Rheumatoid arthritis where generals are prominent. Introduction Rheumatoid arthritis (RA) is the most common  inflammatory arthritis, comes under auto immune  disorder and hence an important cause of potentially preventable disability. Many of the clinical features and management strategies in RA are relevant across the spectrum of inflammatory joint disease. The typical clinical phenotype of RA is a symmetrical, deforming, small and large joint polyarthritis, often associated with systemic disturbance and extra-articular disease. The clinical course is usually life-long, with intermittent exacerbations and remissions and highly variable severity.
Keywords: polyarthritis; clinical; symmetrical; deforming